A New Tolerance Model of Dynamic Thermoelastic Problems for Thin Uniperiodic Cylindrical Shells - TOMCZYK, Barbara; ŚLĘZOWSKI, Bartłomiej (Engineering Transactions, 2017)
The objects of consideration are thin linearly thermo-elastic Kirchhoff-Love-type circular cylindrical shells having a periodically micro-inhomogeneous structure in circumferential direction (uniperiodic shells). The aim of this note is to formulate and discuss a new non-asymptotic averaged model for the analysis of selected dynamic thermoelastic problems for these shells. Contrary to the starting exact shell equations with highly oscillating, non-continuous and periodic coefficients, the proposed tolerance model equations have constant coefficients depending also on a cell size. Hence, an important advantage of this model is that it makes it possible to investigate the effect of a period of inhomogeneity on the global shell thermodynamics (the length-scale effect). This effect is neglected in the known homogenized models derived by asymptotic methods.